The Effect of Specific Risk in Various Stages of the Life Cycle of Companies Listed on the Tehran Stock Exchange. (3rd October 2022) - Ebadi, Mostafa; Azinfar, Kaveh; Dadashi, Iman; Fallah, Reza
Abstract : This research aims to examine the specific risk of companies and their effectiveness in various stages of the company life cycle on state and nonstate ownership. For this purpose, the specific risk was estimated using Fama and French three-factor models, and the research objective was examined by considering the data panel model during the period 2015 to 2020 in a statistical sample consisting of 136 companies active in the Tehran Stock Exchange. For this purpose, the main contribution of research is evaluation of the effect of specific risk in different stages of the life cycle of companies admitted to the Tehran Stock Exchange. Therefore, the main valuable advantage to helping stock managers is assessing the impact of government ownership and nongovernment ownership on the specific risk of companies at different stages of the life cycle. Also, presenting a model to show the effects of dependent and independent variables in order to evaluate the impact of government and nongovernment ownership. The research results confirmed that the specific risk of the company in the stages of introduction, growth, and decline is higher compared to the stages of maturity and stagnation of the life cycle of companies listed on the Tehran Stock Exchange. Because the coefficients of virtual variables related to the life cycle stages of the company are estimated to be significant. Also, the finding confirmed that government ownership significantly affects the relationship between firm risk and life cycle stages in companies listed on the Tehran Stock Exchange. Because, the coefficient of variable state ownership is negative and significant, indicating a lower specific risk in state-owned companies than in nonstate-owned companies.